A pandemic treaty, revised international health regulations, or both? - Labonté, Ronald; Wiktorowicz, Mary; Packer, Corinne; Ruckert, Arne; Wilson, Kumanan; Halabi, Sam (Université d'Ottawa | University of Ottawa, 2021)
Abstract Background A special session of the World Health Assembly (WHA) will be convened in late 2021 to consider developing a WHO convention, agreement or other international instrument on pandemic preparedness and response – a so-called ‘Pandemic Treaty’. Consideration is given to this treaty as well as to reform of the International Health Regulations (IHR) as our principal governing instrument to prevent and mitigate future pandemics. Main body Reasons exist to continue to work with the IHR as our principal governing instrument to prevent and mitigate future pandemics. All WHO member states are party to it. It gives the WHO the authority to oversee the collection of surveillance data and to issue recommendations on trade and travel advisories to control the spread of infectious diseases, among other things. However, the limitations of the IHR in addressing the deep prevention of future pandemics also must be recognized. These include a lack of a regulatory framework to prevent zoonotic spillovers. More advanced multi-sectoral measures are also needed. At the same time, a pandemic treaty would have potential benefits and drawbacks as well. It would be a means of addressing the gross inequity in global vaccine distribution and other gaps in the IHR, but it would also need more involvement at the negotiation table of countries in the Global South, significant funding, and likely many years to adopt. Conclusions Reform of the IHR should be undertaken while engaging with WHO member states (and notably those from the Global South) in discussions on the possible benefits, drawbacks and scope of a new pandemic treaty. Both options are not mutually exclusive.